Guidelines for the assessment of general damages in personal injury cases - Justice Bell (Oxford University Press, 2002)
The Guidelines are designed to provide a clear and logical framework for the assessment of damages while leaving the discretion of the assessor unfettered, since every case must depend to a degree on its own facts. They provide an invaluable guide to all those involved in personal injury litigation: solicitors, barristers, insurance companies, trade unions, and the medical defence organizations